2019
DOI: 10.1093/cdn/nzy097
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-l-Cysteine Supplement in Early Life or Adulthood Reduces Progression of Diabetes in Nonobese Diabetic Mice

Abstract: Background Oxidative stress contributes to the pathologic process leading to the development, progression, and complications of type 1 diabetes (T1D). Objective The aim of this study was to investigate the effect of the antioxidant N-acetyl-l-cysteine (NAC), supplemented during early life or adulthood on the development of T1D. Methods NAC was administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…Charron et al [ 85 ] also demonstrated that in high-fat diet-fed maternal mice, n-acetylcysteine supplementation in the maternal stage decreased diabetes mellitus development in offspring. A similar effect was also demonstrated in a type 1 diabetes mellitus animal model under insulin deficiency[ 86 ]. N-Acetylcysteine also lessened organophosphate-mediated toxicity in vivo .…”
Section: Role Of Ros Generation In Organophosphate-mediated New-onset Diabetes Mellitussupporting
confidence: 70%
“…Charron et al [ 85 ] also demonstrated that in high-fat diet-fed maternal mice, n-acetylcysteine supplementation in the maternal stage decreased diabetes mellitus development in offspring. A similar effect was also demonstrated in a type 1 diabetes mellitus animal model under insulin deficiency[ 86 ]. N-Acetylcysteine also lessened organophosphate-mediated toxicity in vivo .…”
Section: Role Of Ros Generation In Organophosphate-mediated New-onset Diabetes Mellitussupporting
confidence: 70%
“…Moreover, glucose reduces ROS levels in a dose-dependent manner [183], thus enabling proper secretion of insulin. We also found that low concentrations of 5 µM H 2 O 2 , which is within the physiological range, inhibited insulin secretion under low-glucose conditions, while insulin secretion, stimulated by high-glucose levels, was not impaired [184]. Cell death was observed only with higher doses of H 2 O 2 (100 µM), suggesting that the negative effect of H 2 O 2 on insulin secretion is mediated by redox regulation of the process, rather than an outcome of oxidative stress damage.…”
Section: Redox Regulation Of Insulin Secretionsupporting
confidence: 50%
“…It’s the only antioxidant drug to have clinical utility in improving a renal condition whose pathologic mechanism may involve oxidative stress. A pilot study demonstrated that NAC could not reduce serum biomarkers of oxidant stress in patients with diabetic proteinuria [ 134 ] even though preclinical studies have shown cardiovascular benefits or reduced progression of diabetes attributed to NAC-mediated inhibition of ROS production [ 137 , 138 , 139 ]. Intake of the fat-soluble vitamin E, known to be deficient in diabetes, was reported to be significantly associated with reduced risk of type 2 diabetes [ 140 ].…”
Section: Implication Of Oxidative Stress In Diabetes Related Complica...mentioning
confidence: 99%